Epigenetic Regulation in Pathology of Atherosclerosis: A Novel Perspective - Tang, Haishuang; Zeng, Zhangwei; Shang, Chenghao; Li, Qiang; Liu, Jianmin (Frontiers in Genetics, 2021)
Cardiovascular diseases are one of the main causes of human death worldwide. Atherosclerosis, characterized by atherosclerotic plaques, can be seen as a chronic inflammatory disease. The rupture of atherosclerotic plaque can induce deadly accidents, such as ischemic stroke and myocardial infarction. The pathology of atherosclerosis is complex which involves different cell types. Recently, numerous researches have evidenced the close relationship between atherosclerosis and epigenetic regulation, which includes DNA methylation, histone modifications, and non-coding RNA modification. Epigenetic regulations in atherosclerosis provide us with a novel perspective in researching mechanisms and finding novel therapeutic targets of this serious disease. Here, we review the recent discoveries between epigenetic regulation mechanisms in atherosclerosis.